2010
DOI: 10.1128/jb.01620-09
|View full text |Cite
|
Sign up to set email alerts
|

Flagellated but Not Hyperfimbriated Salmonella enterica Serovar Typhimurium Attaches to and Forms Biofilms on Cholesterol-Coated Surfaces

Abstract: The asymptomatic, chronic carrier state of Salmonella enterica serovar Typhi occurs in the bile-rich gallbladder and is frequently associated with the presence of cholesterol gallstones. We have previously demonstrated that salmonellae form biofilms on human gallstones and cholesterol-coated surfaces in vitro and that bile-induced biofilm formation on cholesterol gallstones promotes gallbladder colonization and maintenance of the carrier state. Random transposon mutants of S. enterica serovar Typhimurium were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 108 publications
8
96
0
Order By: Relevance
“…As cholesterol is the primary constituent of human cholesterol gallstones, cholesterolcoated Eppendorf tubes have been employed to mimic human gallstones in vitro, and Salmonella has been shown to form biofilms on these tubes (Crawford et al, 2008). Screening of a random transposon bank for mutants that were impaired in biofilm formation on cholesterol-coated Eppendorf tubes led to the identification of 49 mutants with this phenotype (Crawford et al, 2010a). The results revealed that genes involved in flagellum biosynthesis and structure primarily mediated attachment to cholesterol (Crawford et al, 2010a).…”
Section: Gel Electrophoresis Analyses By Vanmentioning
confidence: 99%
See 1 more Smart Citation
“…As cholesterol is the primary constituent of human cholesterol gallstones, cholesterolcoated Eppendorf tubes have been employed to mimic human gallstones in vitro, and Salmonella has been shown to form biofilms on these tubes (Crawford et al, 2008). Screening of a random transposon bank for mutants that were impaired in biofilm formation on cholesterol-coated Eppendorf tubes led to the identification of 49 mutants with this phenotype (Crawford et al, 2010a). The results revealed that genes involved in flagellum biosynthesis and structure primarily mediated attachment to cholesterol (Crawford et al, 2010a).…”
Section: Gel Electrophoresis Analyses By Vanmentioning
confidence: 99%
“…Screening of a random transposon bank for mutants that were impaired in biofilm formation on cholesterol-coated Eppendorf tubes led to the identification of 49 mutants with this phenotype (Crawford et al, 2010a). The results revealed that genes involved in flagellum biosynthesis and structure primarily mediated attachment to cholesterol (Crawford et al, 2010a).…”
Section: Gel Electrophoresis Analyses By Vanmentioning
confidence: 99%
“…Interestingly, however, formation of Salmonella biofilms on gallstones is dependent on the presence of bile (Prouty et al, 2002). Bile is known to interact and manipulate gene expression in Salmonella biofilms, such as downregulating SPI-1 genes and mobility genes (Crawford et al, 2010;Prouty & Gunn, 2000). Despite this, the effects are believed to be minimal and may not dramatically affect the abilitiy of Salmonella's to invade via effectors of SPI-1 or migrate via flagella.…”
Section: Persistencementioning
confidence: 96%
“…Furthermore, transposon mutagenesis of S. Typhimurium in flagellar hook-associated protein and lipopolysaccharide synthesis severely altered attachment to meat and poultry and biofilm formation on different surfaces (21). In a more recent study with S. Typhimurium motA, fliC, fljB, and fliC fljB mutants, it was concluded that flagellar motility does not affect biofilm formation on cholesterol surfaces, but fliC expression does (22).…”
Section: Figmentioning
confidence: 99%